Crisis Reporters, Emotions, and Technology An Ethnography - Kotišová, Johana (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This open access book explores the emotional labour of crisis reporters in an original style that combines fictional and factual narrative. Exploring how journalists make sense of their emotional experience and development in relation to their professional ideology, it illustrates how media professionals learn to think and act within crisis situations. Drawing on in-depth interviews with journalists reporting on wars, terror attacks and natural disasters, the book rethinks traditional concepts in journalistic thought. Finally, it reflects on the specific, contemporary vulnerabilities of industry professionals, including the impact of new technologies, specific forms of precarity, and a particular strain of cynicism central to the industry. Combining comprehensive, empirical research with the fictional narrative of a journalist protagonist, Crisis Reporters, Emotions and Technology establishes an innovative approach to academic storytelling.